PENGARUH SIFAT KEPRIBADIAN DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASIONAL STUDI PADA GURU SMA NEGERI DI KECAMATAN MRANGGEN DEMAK - Kiswati Rahayu Winarni, 12.5202.0015; Liana, Lie (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to examine the influence of personality traits and emotional intelligence on the performance of teachers in the mediation of organizational commitment to high schools in the District Mranggen. The research involved 95 teachers in the public high school in Mranggensubdistrict The data collected by sending questionnaire to respondents.and analyzed using SPSS 19.0 Data processing is done by describing the respondents by gender, education, age and years of service, all the respondent are teachers. By using the validity and reliability,test models used to analyze the coefficient of determination (R2) and the Goodness of fit. Meanwhile test hypothesis test using a significance test of individual parameters (statistical t test). The results showed that the of personality traits had no effect on organizational commitment, emotional intelligence had no Â positive effect on organizational commitment, personality traits positive effect on teacher performance, and emotional intelligence had no effect on teacher performance, while organizational commitment result also hasnât effect on the performance of teachers. Keywords : Personality Traits, Emotional Intelligence, Organizational commitment and Teacher Performa